Exploring Cancer Pain Self-Management Needs and Preferences: A Meta-Ethnography. (July 2021) - Anderson, Alice; Starkweather, Angela; Cong, Xiaomei; Kyounghae, Kim; Judge, Michelle; Schulman-Green, Dena
Self-management of chronic disease and related symptoms provides a framework for understanding the contextual factors that influence self-management knowledge and skills that patients and families require to manage their condition on a day-to-day basis. The management of cancer pain is a significant issue for patients and families, and their experience can provide insight on cancer pain self-management support needs and preferences. A meta-synthesis of 20 qualitative research articles on self-management of cancer pain was conducted to gain a deeper understanding of the self-management support needs of patients with cancer pain. Noblit and Hare's meta-ethnographic model was used. The meta-synthesis resulted in increased understanding of the needs and preferences for self-management support of cancer pain and the role of the health care practitioner. Practical implications are presented.